Classifying GBL: Severity And Attrition. Is There Enough Bone To Reconstruct The Glenoid?. Issue 7 (29th July 2014) - McNeil, John William; Bernhardson, Andrew; LeClere, Lance E.; Dewing, Christopher; Lynch, Joseph; Gaston, Tistia; Provencher, Matthew
Objectives: Glenoid bone loss (GBL) continues to be a challenge in the management of recurrent anterior shoulder instability. Although the location of and percentage of GBL has been described, there is little information on how much bone is left to reconstruct the glenoid. Thus, the objective of this study is to describe a new GBL classification system that accounts for type of bone defect, amount of attritional loss, and correlate this to age, total time of instability and number of instability events. Methods: A total of 140 patients with recurrent anterior instability underwent an analysis of computed tomography (CT) three-dimensional imaging to assess GBL. The glenoid bone fragment was digitally analyzed (Osirix, Adobe) to qualitatively and quantitatively stratifyeach patient based upon attrition into- Type I "minimal atrittional" (no attrition -33%), Type II "partial attritional" (34 - 66%), and Type III "severe attritional" (67% - complete attrition). Additionally, demographic variables of age, total time of instability, and number of instability events were correlated to type of bone loss. Results: Patients had a mean age of 30.6 (range: 20 - 54) with a demonstrated mean GBL of 16.5% (range 5.1 - 62.3). Furthermore, the mean size of the remaining glenoid bone fragment was 27.8% of the full fragment size. Of 140 participants, 12 had attritional bone loss classified as Type I (12/140 = 8.6% of patients), 45 as Type II (45/140 = 32.1%), and 83 as Type III (83/140 = 59.3%). The mean percent loss for these three categories was 22.2%, 54.4%, and 88.5% respectively. Longer time of instability and more dislocations were associated with type III bone loss, and higher attrition of bone loss. Conclusion: This study highlights that GBL presents in a highly attritional nature and one should be cognizant that the remaining bone fragment does not come close to reconstituting glenoid bone stock. Patients with recurrent instability are predominantly severe attritional (Type III).